PERANCANGAN DAN IMPLEMENTASI SISTEM INFORMASI MANAJEMEN KEUANGAN SEKOLAH (STUDI PADA YAYASAN PENDIDIKAN BUNAYYA TAHFIDZUL QUR'AN KENDAL) - Miftahurrohman Miftahurrohman; Shinta Sabna Kartika Shinta (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2023)
One of the factors that affect the quality of education is the ability of schools to manage school financial resources effectively and efficiently and by balancing the flow of incoming and outgoing funds. School financial management is managed in a transparent and accountable manner which is the basic principle of school financial management. The obstacle that often occurs in school financial management is that it is done manually, where each transaction is recorded in the cash receipts book and cash disbursement book and then recaps are carried out to produce periodic reports. The design and implementation of a school management information system to facilitate school financial management with automated processes can help facilitate school financial management. So that school financial management is carried out in a transparent, accountable, effective and efficient manner. the school's financial management information system also produces information presented in reports as a basis for decision making and the supervisory function can be properly managed